Various Sources Working Capital Financing For The Sustainability Micro, Small And Medium Enterprises (MSMEs) Business In Rancabungur-Bogor - Indra Siswanti; Lenny Christina Nawangsari (Jurnal Abdimas Perbanas, 2023)
Micro, Small and Medium Enterprises (MSMEs) are the object of community service activities, which are located in the Rancabungur area, West Java. Small, Micro and Medium Enterprises (MSMEs) businesses need to understand various alternative sources of working capital financing, so that it is hoped that micro, small and medium enterprises (MSMEs) can find solutions to financing working capital within the framework of development and maintenance of the business in order to continue to be sustainable. The purpose of this community service activity is to provide training for micro, small and medium enterprises (MSMEs) to get various alternative sources of financing both from commercial banks/Islamic banks or from non-bank financial institutions. For this reason, activities team community service Universitas Mercu Buana Jakarta with the topic: “MSMEs Management Development of Achieve Business Sustainability Viewed from Various Management Perspectives (Marketing, Finance, Human Resources, and Operation)”